2020
DOI: 10.1103/physrevb.102.014439
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spin fluctuations in the frustrated A -site spinel CuAl2O4

Abstract: We performed nuclear magnetic resonance (NMR) and muon spin relaxation (μSR) experiments to identify the magnetic ground state of the frustrated quantum A-site spinel, CuAl 2 O 4 . Our results verify that the ground state does not exhibit a long-range magnetic ordering, but a glasslike transition manifests at T * = 2.3 K. However, the Gaussian shape and the weak longitudinal field dependence of μSR spectra below T * show that the ground state has dynamic spin fluctuations, distinct from those of conventional s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…In all cases the FC susceptibility curve continues to increase below the bifurcation temperature suggesting a portion of the spins not participating in the glassy dynamics. This is consistent with the interpretation suggested by Cho et al 13 for CuAl 2 O 4 that a dynamic and glassy phase coexist with the glassy phase corresponding to the degree of site disorder. Further, the applied magnetic field dependent bifurcation temperature deviates from the mean field AT line.…”
Section: Summary and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In all cases the FC susceptibility curve continues to increase below the bifurcation temperature suggesting a portion of the spins not participating in the glassy dynamics. This is consistent with the interpretation suggested by Cho et al 13 for CuAl 2 O 4 that a dynamic and glassy phase coexist with the glassy phase corresponding to the degree of site disorder. Further, the applied magnetic field dependent bifurcation temperature deviates from the mean field AT line.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…Parameters derived from this model fit within ranges for both insulating spin glasses and cluster glasses, although with the higher spin flip times reported in Table 3 we lean towards an insulating spin glass. Therefore, we believe the best interpretation of our solid solution from this analysis is that of a spin glass-like system shifting from a dilute diamond lattice to a dilute pyrochlore as Al is replaced with Ga 13 , 45 , with weaker frustration as Cu 2+ shifts to the pyrochlore lattice and bond length increases.…”
Section: Summary and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our previous experimental works [18,19] and theoretical study [20,21] suggested a cuprate system CuAl2O4 (with Cu 2+ in tetrahedra, having e 4 t2 5 electron configuration) as a strong candidate hosting the Jeff=1/2 state. As the Cu 2+ ion has the largest U and λ, among other magnetic 3d transition metals [4,5], the cuprate compound would be an excellent example to introduce the SOE state with a strong correlation.…”
mentioning
confidence: 97%
“…CuAl2O4 has a spinel structure (Fig. 1a), where Cu 2+ is located at the center of the tetrahedron (A-site) [18,19]. Al 3+ sits at the center of the octahedra that consists of six neighboring oxygen ions (B-site).…”
mentioning
confidence: 99%